2019
DOI: 10.1186/s12889-019-7034-4
|View full text |Cite
|
Sign up to set email alerts
|

How to increase public participation in advance care planning: findings from a World Café to elicit community group perspectives

Abstract: Background In 2014, Alberta, Canada broke new ground in having the first provincial healthcare policy and procedure for advance care planning (ACP), the process of communicating and documenting a person’s future healthcare preferences. However, to date public participation and awareness of ACP remains limited. The aim of this initiative was to elicit community group perspectives on how to help people learn about and participate in ACP. Methods Targeted invitations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 25 publications
2
49
0
3
Order By: Relevance
“…Canada, Australia, and Japanese studies have shown that the legislative and nongovernmental organizations (NGOs) are important drivers of ACP development. [19][20][21] The success of ACP development in Hongkong and Taiwan, 22,23 many of which experience is worth learning. From public awareness to gradually practice to legislative support, in mainland China, it is in this regard that LWPA as NGOs can push forward the process, the promotion will be intended to conduct using a method of combining online services and offline services.…”
Section: Discussionmentioning
confidence: 99%
“…Canada, Australia, and Japanese studies have shown that the legislative and nongovernmental organizations (NGOs) are important drivers of ACP development. [19][20][21] The success of ACP development in Hongkong and Taiwan, 22,23 many of which experience is worth learning. From public awareness to gradually practice to legislative support, in mainland China, it is in this regard that LWPA as NGOs can push forward the process, the promotion will be intended to conduct using a method of combining online services and offline services.…”
Section: Discussionmentioning
confidence: 99%
“…These aspects will be studied using two different activities. First, a qualitative technique called “World Cafe” [ 52 ] which will consist of gathering a sample of the participating agents (teachers, management teams, parents and schoolchildren) and dividing them into three different groups: (1) teachers and management team, (2) parents, and (3) schoolchildren. Each of the groups will be accompanied by someone from the research team, who will act as a moderator of the table, guiding the conversation through a script of semi-structured questions.…”
Section: Methodsmentioning
confidence: 99%
“…26,27 For example, more than 90% of Americans believed it was important to talk about their wishes with a loved one however less than 30% had initiated this conversation, believing it was not the right time and not something they felt they needed to worry about at that stage. 23 In an attempt to normalise the conversation and increase public engagement, several social media forums 5 and community promotion initiatives have been launched. 28,29 Yet evidence 18 suggests comfort levels around these discussions depend on one's personal experience with death and dying as well as their knowledge of advance care planning.…”
Section: Introductionmentioning
confidence: 99%